Effects of Fire on Grassland Soils and Water : A Review - Neary, Daniel G. George (2022)
Grasslands occur on all of the continents. They collectively constitute the largest ecosystem in the world, making up¬†40.5% of the terrestrial land area, excluding Greenland and Antarctica. Grasslands are not entirely natural because they have formed and developed under natural and anthropogenic pressures. Their importance now is to the variety of ecosystem services that they provide: livestock grazing areas, water catchments, biodiversity reserves, tourism sites, recreation areas, religious sites, wild food sources, and natural medicine sources. An important function of grasslands is their sequestration and storage of carbon (C). Mollisol soils of grasslands have deep organic matter horizons that make this vegetation type almost as important as forests for C fixation and storage. Fire has been and continues to be an important disturbance in grassland evolution and management. Natural wildfires have been a component of grasslands for over 300 million years and were important in creating and maintaining most of these ecosystems. Humans ignited fires over many millennia to improve habitat for animals and livestock. Prescribed fire practiced by humans is a component of modern grassland management. The incidence of wildfires in grasslands continues to grow as an issue as droughts persist in semi-arid regions. Knowledge of fire effects on grasslands has risen in importance to land managers because fire, as a disturbance process, is an integral part of the concept of ecosystem management and restoration ecology. Fire is an intrusive disturbance in both managed and wildland forests and grasslands. It initiates changes in ecosystems that affect the composition, structure, and patterns of vegetation on the landscape. It also affects the soil and water resources of ecosystems that are critical to overall ecosystem functions and processes.